Konservasi Yang Hidup Dalam Ritual: Kajian Etnobiologi Upacara Kede Pada Masyarakat Adat Detupera - Maria Serlina Pawe; Maria Magdalena Vannessa Lura; Veronika P Sinta Mbia Wae (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
ThisÂ articleÂ discussesÂ theÂ “Kedeâ€Â traditionalÂ ceremonyÂ asÂ aÂ formÂ ofÂ localÂ wisdom-basedÂ conservationÂ thatÂ isÂ stillÂ preservedÂ byÂ theÂ DetuperaÂ indigenousÂ community,Â EndeÂ Regency.Â ThroughÂ anÂ ethnobiologicalÂ approach,Â thisÂ researchÂ examinesÂ theÂ symbolism,Â ritualÂ structure,Â andÂ ecologicalÂ valuesÂ containedÂ inÂ theÂ traditionalÂ practice.Â TheÂ “Kedeâ€Â ceremonyÂ reflectsÂ theÂ spiritualÂ relationshipÂ betweenÂ humans,Â ancestorsÂ andÂ nature,Â andÂ containsÂ customaryÂ rulesÂ thatÂ supportÂ theÂ sustainableÂ preservationÂ ofÂ naturalÂ resources.Â TheÂ resultsÂ showÂ thatÂ theÂ useÂ ofÂ localÂ plantsÂ suchÂ asÂ leke,Â denu,Â kelaÂ andÂ leluÂ hasÂ symbolicÂ meaningsÂ thatÂ strengthenÂ environmentalÂ conservationÂ andÂ biodiversityÂ preservation.Â ThisÂ ritualÂ alsoÂ functionsÂ asÂ anÂ intergenerationalÂ ecologicalÂ educationÂ systemÂ withinÂ theÂ indigenousÂ community.Â Therefore,Â theÂ “Kedeâ€Â ceremonyÂ canÂ beÂ aÂ contextualÂ conservationÂ modelÂ thatÂ integratesÂ culturalÂ values,Â spirituality,Â andÂ ecologicalÂ ethicsÂ inÂ maintainingÂ theÂ balanceÂ ofÂ nature.KataÂ Kunci:Â Konservasi,Â UpacaraÂ Adat,Â Etnobiologi,Â KearifanÂ Lokal,Â RitualÂ